Risk-managed time-series momentum: An emerging economy experience - Simarjeet Singh; Nidhi Walia; Stelios Bekiros; Arushi Gupta; Jigyasu Kumar; Amar Kumar Mishra (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - This research study aims to design a novel risk-managed time-series momentum approach. The present study also examines the time-series momentum effect in the Indian equity market. Apart from this, the study also proposes a novel risk-managed time-series momentum approach. Design/methodology/approach - The study considers the adjusted monthly closing prices of the stocks listed on the Bombay Stock Exchange from January 1996 to December 2020 to formulate long-short portfolios. Newey-West t statistics were used to test the significance of momentum returns. The present research has considered standard risk factors, i.e. market, size and value, to evaluate the risk-adjusted performance of timeseries momentum portfolios. Findings - The present research reports a substantial absolute momentum effect in the Indian equity market. However, absolute momentum strategies are exposed to occasional severe losses. The proposed time-series momentum approach not only yields 2.5 times higher return than the standard time-series momentum approach but also causes substantial enhancement in downside risks and higher-order moments. Practical implications - The study's outcomes offer valuable insights for professional investors, capital market regulators and asset management companies. Originality/value - This study is one of the pioneers attempting to test the time-series momentum effect in emerging economies. Besides, current research contributes to the escalating literature on risk-managed momentum by suggesting a novel revised time-series momentum approach.
Keywords: G12; G13; 330; Time-series momentum; Risk-managed time-series momentum; Indian stock market